Sustainable Development of Mountain Tourism: Reading Mountaineering Narratives from Sherpa and Non-Sherpa Perspectives - Upadhyay, Toya Nath (SCHOLARS: Journal of Arts & Humanities, 2025)
After Nepal allowed Mount Everest ascent for foreigners in the 1950s, the number of climbing enthusiasts has been mushrooming each year. The growing number has considerably contributed to the economic development of the local Sherpas and the Nepal government alike. But it has concurrently brought threats to the local culture and the environment, which has consequently drawn serious attention of the locals, environmentalists, policy makers, and writers. The mountaineering writers, Jamling Tenzing Norgay and Jon Krakauer have raised voice for the environmental concern in their narratives: Touching My Father’s Soul and Into Thin Air respectively. My paper aims at exploring how these authors express their views on sustainable mountain tourism, environmental reverence, and cultural preservation through their narratives. After analyzing the narratives from the perspective of responsible tourism and Sherpa spirituality (based on Tibetan Buddhism), the paper finds out that both authors show concerns on the onslaughts induced by commercialization of Everest tourism such as untimely casualties, environmental degradation, and cultural impacts. The paper concludes that both authors, being aware of such detrimental effects of mountain tourism, call for a responsible tourism that works for the development of socio-cultural, economic and environmental dimensions of sustainable tourism in the destination area. But, while, for Norgay, sustainability is attenable through the teachings of Tibetan spirituality, for Krakauer, it is through effective tourism policies. Finally, reading these texts from this perspective, the study expects to add a critical reading into the relationship among mountain tourism, Sherpa culture, and environmental reverence.